Correlates of protection induced by live Aro- Salmonella typhimurium vaccines in the murine typhoid model. - Harrison, J A (1997)
Live attenuated salmonella vaccines generally confer better protection than killed vaccines. The immune responses in BALB/c mice elicited by immunization with a live attenuated Aro Salmonella typhimurium vaccine given orally, intravenously or subcutaneously were compared with those elicited by killed whole-cell vaccines (acetone or heat-treated) given subcutaneously. Live vaccines given by all routes elicited higher interleukin-2 (IL-2) and interferon-gamma (IFN-gamma) responses in spleen cells against an alkali-treated whole-cell salmonella lysate than did killed vaccines. Live and killed vaccines elicited high total antibody levels to smooth lipopolysaccharide (LPS) (enzyme-linked immunosorbent assay), but all live vaccine regimes elicited higher IgG2a, suggesting a Th1 response. Oral and intravenous vaccination with live organisms elicited IgA against smooth LPS which subcutaneous vaccination with live or killed salmonellae failed to evoke. Western blots using rough whole-cell lysates showed that all vaccines elicited a varied anti-protein response; however, all groups immunized with live organisms recognized three unidentified bands of MW 52,000, 46,000 and 18,000 which were consistently absent in groups immunized with killed organisms. The results indicate that immunization with live aroA salmonellae elicited a Th1 type of response, including bystander T-cell help to LPS, and a response to proteins not seen in mice that received killed vaccines.